Pemanfaatan Media Sosial Sebagai Pendukung Siaran Dakwah Di Radio Bhasa Fm Situbondo - Manaf, Abdul; Maraghi, A. Musthofa Al; Hariri, Ahmad Amin Alfan; Fauzi, M. Sholeh Ali; Wisri (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study examines the utilization of social media as a support for Islamic Da’wah broadcasts at Radio Bhasa FM Situbondo. The aim is to analyze the role of social media in expanding the reach of preaching, enhancing listener interaction, and strengthening the radio's presence as a medium for da’wah. The research employs a descriptive qualitative method through interviews, observations, and document analysis. The findings indicate that social media effectively supports broadcasting, facilitates two-way communication, and increases public participation. This study confirms that the integration of radio and social media can serve as an adaptive and participatory model of da’wah communication.